The relationship between emotional intelligence and mathematics performance of preservice teachers in Minna, Niger State - Ahmad, Manko Umar; Zakarriya, Aliyu Alhaji; Isa, Alhassan Diadia (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This study aims to assess the relationship between emotional intelligence and mathematics performance among preservice teachers in Minna, Niger State. The study used a correlation survey design and included 150 participants who were studying for the Nigeria Certificate in Education (NCE). Two instruments, EIMQ and MAT, were developed by the researchers to collect data. The instruments were validated by experts and found to be reliable with an internal consistency of r= 0.76 and 0.85, respectively. Descriptive statistics were used to answer the research questions, and the null hypothesis was analyzed using Pearson Product Moment Correlation (PPMC) at alpha = 0.005 level of significance. The findings show that a significant relationship exists between emotional intelligence and mathematics performance as r = 0.877. Recommendations include educating preservice teachers on emotional intelligence, guiding and supporting learners to develop emotional intelligence, and incorporating emotional skills in the mathematics curriculum.